Duty ratio control ofthree port isolated bidirectional asymmetrical triple active bridge DC-DC converter - Adarsh S; Nagendrappa H (Institute of Advanced Engineering and Science, 2021)
Multiport converters are used in interfacing of distributed energy sources with grid/load. Isolated converters are needed in applications where converter gain is high and there is a requirement of isolation. Dual transformer asymmetric triple active bridge offers the advantage of reduced circulating current. However, the operating range is low for variation in load and source voltage. In this paper duty ratio modulation technique is proposed to regulate the load voltage and control the power flow in both the directions. As a result of the new gating scheme, the converter switches operate with ZVS, irrespective of variations in load power and source voltage. The converter is designed to ensure high switch utilization. The control technique is validatedthrough simulation of a 1kW three port DC-DC converter. It was observerd that the load voltage was regulated for wide range of variation in load power and source port voltages. The single input dual output mode was also verified.